Tutoring and study support for educational success and contrast to the stereotypes. The Sono capace project in the Sinti Village of Tortona (AL) - Andrea Traverso; Giada Finotti (Educazione Interculturale)
The paper presents the experience of the Terre di Mezzo Association in the Sinti Village of Tortona (AL). The project Sono capace has connected a double level: the students of the G. Peano High School of Tortona, engaged as tutors in a work-based learning program (PCTO); an effective action of support to the study of a group of minors (primary and lower secondary school) who live in the nomad camp of Tortona. Furthermore, a third level is the commitment of the association’s educators in organizing recreational-educational activities for all those involved, the high school students, the boys and girls of the village, to enhance the system dimension and promote real inclusion. The effectiveness is monitored in many areas of interest: the development of high school students’ skills - in addition to a change in terms of contrasting prejudices towards Sinti - and school support, for a better adherence to the educational path to protect and contrast dispersion, or simply prolonged periods of absence from school.